Wypędzić poezję, wygnać poetów. Współczesne interpretacje Platońskiego postulatu - Bartol, Krystyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
This article is a critical review of the most important modern interpretations of the Platonic postulate of expelling poets from the polis, formulated in two works of the thinker, the Republic and the Laws. The reflections presented in the article focus on two fundamental questions, namely the reasons behind Plato’s refusal to allow poets into his ideal state and, secondly, the aim he was going to attain by expelling artists from the community of citizens. To try to explain the reasons behind these statements, so embarrassing to present-day readers of Plato, involves considerations of Plato’s concept of the nature of poetry (art as flawed, defective and secondary reflection of the sensual world), as well as of ethical questions (art as a perfidious tool to facilitate malevolent designs towards human characters). Any investigation as to the intentions of the philosophers that preceded the formulation of the postulate concentrates thus inevitably on his vision of utopian realism. It further aims to provide sufficient arguments that Plato, oscillating in his presentation between authoritarian diagnosis and protreptic provocation, makes recipients redefine the mutual relationship between literature and philosophy.